Sosialisasi terhadap Pemberdayaan Remaja Putus Sekolah Di Gampong Suak Bilie Kabupaten Nagan Raya Melalui Pendidikan Entrepreneurship - Ligar Abdillah; Yeni Sri Lestari; Irma Juraida; Devi Intan Chadijah; Lilis Sariyanti; Triyanto Triyanto; Fadli Afriandi; Ikhwan Rahmatika Latif; Muntaha Mardhatillah; Ilham Mirza Saputra (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2022)
The potential of adolescents in education has a huge influence on the development of a better social life, especially in the order of interaction in their daily lives. However, the problem of education equality is still a trigger for high levels of youth unemployment, including one of them in Gampong Suak Bilie. Different reasons for the problem of dropping out of school can be directed by empowering teenagers who drop out of school, this is due to the habits of teenagers who spend more time playing. The method of implementing youth empowerment is through socialization and mentoring adolescents who drop out of school. The results of this service found that adolescents in Gampong Suak Bilie have the potential to develop their interests, but the lack of resources and motivation that support to develop the potential of adolescents results in not accommodating the interests of adolescents.